Regulation and role of mitochondrial Ca2+ homeostasis - Rizzuto, Rosario (Henry Stewart Talks, 2007)
Targeted Calcium indicators, The principles of mitochondrial Calcium accumulation, The role of the outer membrane channel VDAC, The mitochondrial Calcium uniporter of the inner membrane (MCU), The ER-mitochondria contacts, Calcium re-extrusion, ATP measurements, The role of Calcium in mitochondrial functions (aerobic metabolism and apoptosis induction)